DIGITAL TOOLS IN HUMAN RESOURCE MANAGEMENT: HOW DIGITIZATION AFFECTS PERSONNEL MANAGEMENT - Prokopenko, Olha; Garafonova, Olha; Zhosan, Hanna (Socio-economic relations in the digital society, 2023)
This article delves into the dynamic of human resource management (HRM) in the era of digitization, examining the profound influence of digital tools on personnel management practices. Through a meticulous review of literature, theoretical frameworks, and empirical studies, it elucidates the multifaceted impact of digitization on HRM. The study explores how the adoption of digital tools transforms traditional personnel management, addressing key concepts, challenges, and perspectives in the context of digital transformation. Empirical research methods, including surveys, interviews, and focus groups, provide deeper insights into the practical implications of digitization for personnel management. The findings underscore the critical need for organizations to adapt strategically to the digital era, emphasizing the integration of digital technologies to enhance HR processes, employee engagement, talent management, and overall organizational effectiveness. This abstract contributes to the discourse on the intersection of technology and HRM, providing valuable insights for practitioners, scholars, and policymakers navigating the evolution of digitized personnel management.